2007
DOI: 10.1002/mawe.200700214
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir welding of AISI 304 austenitic stainless steel

Abstract: The objective of this work is to demonstrate the feasibility of friction stir welding (FSW) AISI 304 austenitic stainless steels. The tool used was formed of a tungsten-based alloy. The specimens were welded on an 11 kW vertical milling machine. Defect-free welds were produced on 2.5 mm plates of hot-rolled AISI 304 austenitic stainless steels at travel speeds ranging from 40 to 100 mm/ min with a constant rotating speed of 1000 rpm. Tensile strengths and hardness values of the weld interface were determined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 8 publications
1
26
0
1
Order By: Relevance
“…The tensile strength of the welds increased when tilt angle was changed from 0 o to 2 o . C. Meran et al [28] reported that the angle of 0 o caused a serious problem in the weld areas. Small increment on the tilt angle to 2 o helped to increase the joint strength.…”
Section: Figure 4: Effect Of Process Parameters On Uts: (A) Effect Ofmentioning
confidence: 99%
“…The tensile strength of the welds increased when tilt angle was changed from 0 o to 2 o . C. Meran et al [28] reported that the angle of 0 o caused a serious problem in the weld areas. Small increment on the tilt angle to 2 o helped to increase the joint strength.…”
Section: Figure 4: Effect Of Process Parameters On Uts: (A) Effect Ofmentioning
confidence: 99%
“…The fine grain structure increased the hardness and tensile strength in the stir zone [10]. Microstructure and mechanical properties of 304 stainless steel welds made by friction stir welding were evaluated by Meran and Kovan [11]. Higher strength of welding was observed when travel speed is 63mm/min and rotational speed is 1000 rpm.…”
Section: Fig 2:-microstructural Regions Of Friction Stir Welding (Mamentioning
confidence: 99%
“…Higher strength of welding was observed when travel speed is 63mm/min and rotational speed is 1000 rpm. Friction Stir Welding (FSW) was applied to AISI 304 austenitic stainless steels and the effect of different tool rotational speeds, traverse speeds, compressive tool forces, and tool angles was investigated by C.Meran et.al [12]. It is found that the maximum tensile strength is observed with 950 rpm rotational speeds and 60 mm/min traverse speed, 9 kN compressive tool force, and 1.5 0 tool tilt angle [ Fig.3].…”
Section: Fig 2:-microstructural Regions Of Friction Stir Welding (Mamentioning
confidence: 99%
See 1 more Smart Citation
“…Meran and Kovan [5] studied the microstructural features of 304 stainless steel welded plates.. Welding was performed on 11 KW vertical milling machine on 2.5 mm plate. The tool used was tungsten-based alloy they found out that tungsten carbide tool yielded good results.…”
Section: Friction Stir Welding Of Stainless Steel 304: a Surveymentioning
confidence: 99%